The role of innovation in venture capital and private equity investments in different investment phases. Issue 1 (2nd January 2020) - Maas, Cornelius; Steinhagen, Patrick; Proksch, Dorian; Pinkwart, Andreas
ABSTRACT: Innovation is an important value lever, especially within small- and medium-sized companies. However, little research has examined its influence within the investment process of equity investment funds – a surprising circumstance since innovation could increase an investment's value. This study provides insights into equity investment funds' perspective on innovation throughout the various phases of the investment process. We conducted in-depth interviews with investment professionals from 30 German-based equity investment funds. Our results show that innovation's importance depends on the strategic orientation of the equity investment fund type. In addition, our study provides an overview of the criteria, methods, and mechanisms equity investment funds use to support innovation. We show that the emphasis of many equity investment funds on innovation during the identification of investment targets is not reflected in the measures the fund later employs to support innovation processes within the portfolio company. This indicates potential for equity investment funds to be more actively involved in the supervision and management of innovation activities of their portfolio companies.